2020
DOI: 10.1086/710353
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Multivariate Responses of Sexual Dimorphism to Direct and Indirect Selection

Abstract: Sexual dimorphism is often assumed to result from balancing the strength of antagonistic selection in favor of dimorphism against the degree of constraint imposed by the shared genome of the sexes, reflected in the B matrix of genetic intersexual covariances. To investigate the totality of forces shaping dimorphism, we reparameterized the Lande equation to predict changes in trait averages and trait differences between the sexes. As genetic constraints on the evolution of dimorphism in response to antagonistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Intuitively, it would make sense that the similarity between G f and G m would impose a genetic constraint. However, Cheng & Houle [20] demonstrated that similarity in male and female covariance matrices coupled with some degree of B matrix asymmetry suggests a greater opportunity for sexual dimorphism in response to sexually concordant selection than to sexually antagonistic selection. Thus, our estimates of the proportion of standing genetic variation that could respond to sexually antagonistic selection represent lower bounds for the potential sexually dimorphic response, as further sexual dimorphism could evolve in response to sexually concordant selection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Intuitively, it would make sense that the similarity between G f and G m would impose a genetic constraint. However, Cheng & Houle [20] demonstrated that similarity in male and female covariance matrices coupled with some degree of B matrix asymmetry suggests a greater opportunity for sexual dimorphism in response to sexually concordant selection than to sexually antagonistic selection. Thus, our estimates of the proportion of standing genetic variation that could respond to sexually antagonistic selection represent lower bounds for the potential sexually dimorphic response, as further sexual dimorphism could evolve in response to sexually concordant selection.…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of the degree of multivariate sexually antagonistic genetic variation in G mf provides insight to the capacity for further response to sexually antagonistic selection [20,52]. The overall percentages of sexually antagonistic genetic variance were estimated with wide, highly overlapping CIs between our two trait categories (table 2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One phenomenon that can maintain genetic variation for fitness-related traits in natural populations is sexual antagonism, where selection favours different alleles within males and females [63]. Yet, the amount and prevalence of sexually antagonistic variation depends on the genetic architecture of dimorphism, which is not well understood [58,64]. Kollar et al [43] used a multivariate approach to examine the genetic basis of sexual dimorphism in a scent-based fertilization syndrome in the moss Ceratodon purpureus.…”
Section: (D) Multivariate Quantitative Genetics: Moving Beyond the Ge...mentioning
confidence: 99%